New Germans ?– Reflections on Migration in Chosen Works by Female Authors of ‘Prose with Polish Roots’ - Szymańska, Eliza (Transfer. Reception Studies, 2019)
The title of this article on the one hand refers to the book by Özlem Topcu, Alice Bota and Khue Pham published in 2012; on the other, it also refers to the publication of Brigitta Helbig-Mischewski and Małgorzata Zduniak-Wiktorowicz from 2016, in which the two researchers use the term ‘young prose’ not only with reference to writers born in Germany in 1970’s and 1980’s, but also to those who have Polish roots. Their common feature is the fact that either they left Poland as small children, or they were born in Germany. It is of particular interestto find the context regarding the answer to the question: in which way, if in any, female authors (Paulina Schulz, Alice Bota, Emilia Smechowski) describe their status of a migrant and what meaning they ascribe to the fact that among the German people, they are ‘the people of migrant origin’. The examination intends to indicate possible strategies of treatment of migrant experience and will attempt to find an answer to the question if the term ‘new Germans’ is indeed adequate in this context.